Modeling and Parameter Optimization for Surface Roughness and Residual Stress in Dry Turning Process - El-Axir, M. H.; Elkhabeery, M. M.; Okasha, M. M. (Engineering, Technology & Applied Science Research, 2017)
The influence of some turning variables and tool overhang on surface roughness parameters and residual stress induced due to machining 6061-T6 aluminum alloy is investigated in this paper. Four input parameters (cutting speed, feed rate, depth of cut and tool overhang) are considered. Tests are carried out by precision turning operation on a lathe. Design of experiment techniques, i.e. response surface methodology (RSM) and Taguchi's technique have been used to accomplish the objective of the experimental study. Surface roughness parameters are measured using a portable surface roughness device while residual stresses are measured employing deflection-etching technique using electrochemical analysis. The results obtained reveal that feed and rotational speed play significant role in determining the average surface roughness. Furthermore, the depth of cut and tool overhang are less significant parameters, whereas tool overhang interacts with feed rate. The best result of surface roughness was obtained using low or medium values of overhang with low speed and /or feed rate. Minimum maximum tensile residual stress can be obtained with a combination of tool overhang of 37 mm with very low depth of cut, low rotational speed and feed rate of 0.188 mm/rev.